2009
DOI: 10.1111/j.1365-2591.2008.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

The properties and applications of chlorhexidine in endodontics

Abstract: Microorganisms and their by-products are considered to be the major cause of pulp and periradicular pathosis. Hence, a major objective in root canal treatment is to disinfect the entire root canal system, which requires that all contents of the root canal system be eliminated as possible sources of infection. This goal may be accomplished using mechanical instrumentation and chemical irrigation, in conjunction with medication of the root canal system between treatment sessions. To reduce or eliminate bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
345
0
32

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(389 citation statements)
references
References 104 publications
(208 reference statements)
12
345
0
32
Order By: Relevance
“…Accordingly, a comparative evaluation of the adhesion of Epiphany and AH Plus endodontic sealers to human root dentin treated with 1% NaOCl or 1% NaOCl+17% EDTA using the push-out test have shown that AH Plus sealer presented greater adhesion to dentin than Epiphany, regardless of the treatment of the root canal walls 7,17) . However, the bond strength of AH Plus was adversely affected by NaOCl+EDTA irrigation (G H+AH ) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a comparative evaluation of the adhesion of Epiphany and AH Plus endodontic sealers to human root dentin treated with 1% NaOCl or 1% NaOCl+17% EDTA using the push-out test have shown that AH Plus sealer presented greater adhesion to dentin than Epiphany, regardless of the treatment of the root canal walls 7,17) . However, the bond strength of AH Plus was adversely affected by NaOCl+EDTA irrigation (G H+AH ) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies have suggested NaOCl and chlorhexidine as irrigation solutions. [2][3][4] However, MTAD is a recently developed irrigating solution that consists of tetracycline, acetic acid and detergent. 5 It has antimicrobial effect 6 and appears to be effective for removing smear layer along the entire length of the prepared root canal.…”
Section: Introductionmentioning
confidence: 99%
“…20 This agent delivers excellent action against gram-positive and gram-negative bacteria, offers 12 weeks of dentine substantivity, and is biocompatible with the periapical tissues. 21 However, studies suggest that chlorhexidine in high concentrations, as that used in this study, poses a potential systemic risk by producing reactive oxygen species (ROS), causing oxidative damage to deoxyribonucleic acid (DNA), and the release of para-chloroaniline, a cytotoxic agent with carcinogenic potential in humans. 22,23 Although Nebacetin ® ointment and Maxitrol ® ointment are not used in dental treatment, they have already established antimicrobial power in their respective uses.…”
Section: Discussionmentioning
confidence: 99%